2006
DOI: 10.1128/jb.188.9.3308-3316.2006
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Control of the Salmonella enterica Flagellar Hook Protein FlgE

Abstract: Previous work suggested that the FlgE (flagellar hook subunit) protein in Salmonella enterica serovar Typhimurium was posttranscriptionally regulated in response to the stage of flagellar assembly. Specifically, the FlgE protein could be detected in flagellar mutants defective at the stages of assembly before or after rod assembly but not in rod assembly mutants, yet flgE mRNA levels were unaffected. To elucidate posttranscriptional mechanisms involved in the coupling of flgE gene expression to hook assembly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…FlgE (hook) was found in cell extracts of a fliE mutant strain but not in flgB, flgC, flgF, flgG, or flgJ mutant strains (21). This was later shown to be due to a defect of FlgE secretion into the periplasm in the fliE mutant strain but not in the flgB, flgC, flgF, flgG, or flgJ mutant strains (22). It was also shown that secretion of FlgD (hook-cap) was dependent on FliE (23,24).…”
mentioning
confidence: 82%
“…FlgE (hook) was found in cell extracts of a fliE mutant strain but not in flgB, flgC, flgF, flgG, or flgJ mutant strains (21). This was later shown to be due to a defect of FlgE secretion into the periplasm in the fliE mutant strain but not in the flgB, flgC, flgF, flgG, or flgJ mutant strains (22). It was also shown that secretion of FlgD (hook-cap) was dependent on FliE (23,24).…”
mentioning
confidence: 82%
“…This export requirement was previously exploited with fusion proteins expressed in E. coli and other bacteria grown in vitro (Broome-Smith et al, 1990; Lee & Hughes, 2006). Here we showed that BlaTEM-1 can also report on protein export directly in DblaC M. tuberculosis.…”
Section: Discussionmentioning
confidence: 61%
“…Ampicillin resistance in FlgE-Bla-exporting cells was assayed as described 13 , with minor modifications described in Methods. Briefly, cells were diluted to D 600 5 0.01, cultured for 4.5 h in LB media containing ampicillin in a series of dilutions ranging from 800 mg ml 21 to 1.56 mg ml 21 , and the minimum inhibitory concentration (MIC) was taken as the lowest ampicillin concentration giving D 600 , 0.05.…”
Section: Methods Summarymentioning
confidence: 99%
“…Cells were deleted for the rod proteins FlgB and FlgC (Fig. 1) to direct the fusion protein into the periplasm, allowing export to be quantified by the MIC (minimum inhibitory concentration) for ampicillin 13 . The MIC value was reduced by uncoupler, from a value of 25 mg ml 21 in the untreated control to about 4 mg ml 21 in 30 mM CCCP (Table 1, and Supplementary Information).…”
mentioning
confidence: 99%